Maxillary sinus lift surgery—with or without graft material? A systematic review - Silva, L. deF. [UNESP] (2016)
The purpose of this systematic review was to perform a comparative analysis of the use or not of graft material in maxillary sinus lift surgery. Relevant studies published in the last 10 years were identified through a search of the PubMed/MEDLINE, ScienceDirect, and Cochrane Library databases and were assessed against the study inclusion and exclusion criteria. The initial search resulted in 1037 articles. After applying the inclusion and exclusion criteria, 16 articles remained. Four hundred and thirty-six patients were followed up over a postoperative period ranging from 6 months to 11 years. In total, 868 implants were installed in 397 maxillary sinuses. The implant survival rate was 96.00% for surgeries performed without graft material and 99.60% for those in which biomaterial was used, within a follow-up period of 48 to 60 months. In conclusion, maxillary sinus lift surgery, with or without graft material, is a safe procedure with a low complication rate and predictable results.